(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To estimate treatment adherence and identify associated factors among outpatients with type 2 diabetes at Ca Mau General Hospital in 2025. Subjects and Methods: A cross-sectional study was conducted on 260 outpatients with type 2 diabetes. Medication adherence was assessed using MMAS-8. Non-pharmacological adherence included lifestyle modification, dietary adherence, and regular follow-up, which were evaluated using a standardized interview questionnaire. Overall treatment adherence was defined as the simultaneous achievement of all four components. Multivariable logistic regression was performed to identify independent associated factors. Results: Overall treatment adherence was 20.38%. Adherence rates for medication use, lifestyle modification, dietary adherence, and regular follow-up were 51.54%, 64.23%, 60.77%, and 89.23%, respectively. Multivariable logistic regression showed that female sex, urban residence, and higher educational level were independently associated with better adherence, whereas increasing age was associated with lower adherence. Conclusion: Overall treatment adherence remained low. Men, older adults, and rural residents should be prioritized in adherence-support interventions.